2022
DOI: 10.1186/s13256-022-03690-3
|View full text |Cite
|
Sign up to set email alerts
|

Optic disc hemorrhage in a young female following mRNA coronavirus disease 2019 vaccination: a case report

Abstract: Background Since the development of the coronavirus disease 2019 vaccine, there have been many reports of its adverse effects. While respiratory symptoms are common, many other symptoms in various organs have been reported. Herein, we report a case of optic disc and retinal hemorrhage that developed immediately after coronavirus disease 2019 vaccination. Case presentation A healthy 18-year-old Japanese female noticed floater in the left eye 1 day a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A previous study documented that 12 patients had retinal hemorrhage approximately two days after mRNA COVID-19 vaccination [ 4 ]. Tsuda et al [ 5 ] reported a case of IHAPSH following mRNA COVID-19 vaccination. Unlike traditional vaccines that employ attenuated or inactivated pathogens, mRNA vaccines directly inject a small portion of mRNA into the body, which prompts the body’s cells to produce a partial or incomplete viral protein.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study documented that 12 patients had retinal hemorrhage approximately two days after mRNA COVID-19 vaccination [ 4 ]. Tsuda et al [ 5 ] reported a case of IHAPSH following mRNA COVID-19 vaccination. Unlike traditional vaccines that employ attenuated or inactivated pathogens, mRNA vaccines directly inject a small portion of mRNA into the body, which prompts the body’s cells to produce a partial or incomplete viral protein.…”
Section: Discussionmentioning
confidence: 99%
“…It can also enter the peripapillary retina and/or penetrate the nerve tissues in the prelaminar portion of the optic disc, reaching the optic cup and spreading to the surface of the optic disc, the super cial layers of the surrounding retina or the vitreous.If the bleeding lasts for a longer period, the hemorrhage in the optic disc and super cial retina may be absorbed. Alternatively, if the bleeding pressure is low and only reaches the subretinal space around the optic disc, it may manifest as a simple peripapillary subretinal hemorrhage.Sibony et al [10] consider that factors such as the contraction force of the extraocular muscles and changes of intraocular pressure during eye movement, the thinning of the sclera in myopic eyes due to stretching, and the traction force of the vitreous all contribute to the vulnerability of the optic disc, leading to bleeding.Kyohei [11] reported a case of optic disc hemorrhage following mRNA COVID-19 vaccine administration. Relevant literature reports that cardiovascular events such as myocarditis and thrombosis can occur after COVID-19 vaccination, and there may be temporary changes in the circulatory dynamics, including vascular spasms [12,13] .Although most of the fundus manifestations associated with COVID-19 infection are related to abnormal coagulation mechanisms, there are still some cases with abnormal bleeding mechanisms.…”
Section: Discussionmentioning
confidence: 99%